Reindeer coat colour variants in Finland - Lauvergne, Jean J.; Nieminen, Mauri (Rangifer, 2010)
A research program based on reindeer coat colour had its first field survey in Finland after the calving season of May 2009. This short notice advances the main observations of the survey where, besides the wild allele, a new mutant could be identified, at least at three colour loci: Agouti (A), White Spotting (S) and White (W). Poron turkin värityypit Suomessa Abstract in Finnish / Lyhennelmä: Tutkimusprojekti poron turkin väreistä alkoi kenttätutkimuksilla Suomessa vasonnan jälkeen toukokuussa 2009. Tämä lyhyt tiedonanto osoittaa, että porolla on villialleelin lisäksi myös uusi mutanttialleeli vähintään kolmessa värilokuksessa: Agouti (A), Täplikäs (S) ja Valkoinen (W). Fargevarianter av reinpels i Finland Abstract in Norwegian / Sammendrag: Et forskningsprosjekt begynte i felt etter kalving i 2009. Resultatene så langt viser at tamreinen har få fargemutanter sammenliknet med forholdet hos andre domestiserte arter